“A strange modernity”: On the contradictions of the neoliberal university - Martin A. Mills (Anuac, 2017)
While many commentators see neoliberalism as a monolithic force changing universities into businesses, in reality its shared veneer of rhetorical vocabulary obscures profound and irresolvable practical contradictions – contradictions that make university life impossible, even in “business” terms.